Is intra-operative gamma probe detection really necessary for inguinal sentinel lymph node biopsy? - Oliveira Filho, Renato Santos de (2000)
CONTEXT: Sentinel node (SN) biopsy has changed the surgical treatment of malignant melanoma. The literature has emphasized the importance of gamma probe detection (GPD) of the SN. OBJECTIVE: Our objective was to evaluate the efficacy of patent blue dye (PBD) and GPD for SN biopsy in different lymphatic basins. DESIGN: Patients with cutaneous malignant melanoma in stages I and II were submitted to biopsy of the SN, identified by PBD and GPD, as part of a research project. SETTING: Patients were seen at Hospital São Paulo by a multidisciplinary group (Plastic Surgery Tumor Branch, Nuclear Medicine and Pathology). PATIENTS: 64 patients with localized malignant melanoma were studied. The median age was 46.5 years. The primary tumor was located in the neck, trunk or extremities. INTERVENTIONS: Preoperative lymphoscintigraphy, lymphatic mapping with PBD and intraoperative GPD was performed on all patients. The SN was examined by conventional and immunohistochemical staining. If the SN was not found or contained micrometastases, only complete lymphadenectomy was performed. MAIN MEASUREMENTS: The SN was identified by PBD if it was blue-stained, and by GPD if demonstrated activity five times greater than the adipose tissue of the neighborhood. RESULTS: Seventy lymphatic basins were explored. Lymphoscintigraphy showed ambiguous drainage in 7 patients. GPD identified the SN in 68 basins (97%) and PBD in 53 (76%). PBD and GPD identified SN in 100% of the inguinal basins. For the remaining basins both techniques were complementary. A metastatic SN was found in 10 basins. Three patients with negative SN had recurrence (median follow-up = 11 months). CONCLUSION: Although both GPD and PBD are useful and complementary, PBD alone identified the SN in 100% of the inguinal lymphatic basins.